2018
DOI: 10.1186/s12933-018-0797-6
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin on top of metformin treatment improves arterial function in patients with type 1 diabetes mellitus

Abstract: BackgroundDeteriorated arterial function and high incidence of cardiovascular events characterise diabetes mellitus. Metformin and recent antidiabetic drugs, SGLT2 inhibitors, reduce cardiovascular events. We explored the possible effects of empagliflozin’s effect on top of metformin treatment on endothelial function and arterial stiffness parameters in type 1 diabetes mellitus (T1DM) patients.MethodsForty T1DM patients were randomised into three treatment groups: (1) empagliflozin (25 mg daily), (2) metformin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 28 publications
(36 reference statements)
4
70
1
5
Order By: Relevance
“…Researchers concluded that SGLT‐2 inhibitor‐mediated reduction in blood pressure and body weight, improvement of glycemia, and suppression of oxidative stress might contribute to the observed decrease in PWV . In a more recent RCT enrolling 40 patients with T1DM, it was shown that administration of empagliflozin or empagliflozin/metformin combination for 12 weeks decreased arterial stiffness by 14.3% and 15.8% ( P < .01), respectively, compared to placebo, which did not induce any change . An interesting point is that both empagliflozin and empagliflozin/metformin combination had the same effect on endothelial function, as assessed by flow‐mediated dilation (FMD) and reactive hyperemia index (RHI), leading to the conclusion that the observed improvement in arterial stiffness with empagliflozin might be independent of its effect on endothelial dysfunction …”
Section: Sglt‐2 Inhibitors and Arterial Stiffness: A New Place Undermentioning
confidence: 99%
“…Researchers concluded that SGLT‐2 inhibitor‐mediated reduction in blood pressure and body weight, improvement of glycemia, and suppression of oxidative stress might contribute to the observed decrease in PWV . In a more recent RCT enrolling 40 patients with T1DM, it was shown that administration of empagliflozin or empagliflozin/metformin combination for 12 weeks decreased arterial stiffness by 14.3% and 15.8% ( P < .01), respectively, compared to placebo, which did not induce any change . An interesting point is that both empagliflozin and empagliflozin/metformin combination had the same effect on endothelial function, as assessed by flow‐mediated dilation (FMD) and reactive hyperemia index (RHI), leading to the conclusion that the observed improvement in arterial stiffness with empagliflozin might be independent of its effect on endothelial dysfunction …”
Section: Sglt‐2 Inhibitors and Arterial Stiffness: A New Place Undermentioning
confidence: 99%
“…Despite the positive results from clinical trials and evidence‐based guideline recommendations for the use of SGLT2 inhibitors, the precise mechanisms underlying the cardiorenal protective effects of these agents remain to be fully elucidated. A number of beneficial cardiovascular effects of SGLT2 inhibitors have been investigated, including reductions in blood pressure (BP), 6,7 attenuation of the salt sensitivity of BP, 8 improvements in arterial stiffness, 9 and sympatholytic effects 8 . We recently demonstrated that SGLT2 inhibitors significantly reduced out‐of‐office BP determined using ambulatory or home BP monitoring compared with placebo or control in patients with type 2 diabetes and uncontrolled nocturnal hypertension (a salt‐sensitive hypertension phenotype) 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…The trial was done on 40 patients for 12 weeks. The results showed a marked improvement in all assessments [19].…”
Section: Effect Of Sglt2 Inhibitors On Arterial Efficacymentioning
confidence: 84%